OPTIMIZATION OF TECHNOLOGICAL MEANS FOR BULB ONION SEED PRODUCTION - N.V. Moiysevich (Овощи России)
The results presented in the article concerns the optimization of main technological means of bulb onion seed production in Byelorussia. The production mother bulbs from seeds and planting onion are highlighted in the article. Influence of both diameter of mother bulbs and density of grown plants on yield capacity and sowing quality of seeds has been identified. The comparative assessment of seed production in triennial and biennial cultivation has been carried out.